2010
DOI: 10.1002/er.1808
|View full text |Cite
|
Sign up to set email alerts
|

The performance of cathode material of perovskite-like La-Ni-M-O for low temperature solid oxide fuel cell

Abstract: SUMMARYThe low temperature solid oxide fuel cells have recently drawn much more attention due to reducing the corrosion, easing the sealing and avoiding the large hot stress cycling and high costs. In this circumstance, the overpotential of polarization in the cathode will become large and the conductivity will become much lower with reducing the temperature. A novel type of La 2 Ni x M 1-x O 4 (x 5 0.2-0.5) (M 5 Cu, Co) perovskite-like oxide was synthesized and studied as the cathode for low-temperature, 400-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Amphoteric electrode metal oxides easily dissolve in acidic or basic environments. Strategies to circumvent the poor stability of metal oxide electrodes involve control of the melt oxobasicity with admixtures (eg, rare earth or alkaline carbonates/oxides), but also formation of solid solutions based on conventional NiO with other metals . The state‐of‐the art solutions show some efficacy, but alternative materials with high conductivity and chemically stable are still needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphoteric electrode metal oxides easily dissolve in acidic or basic environments. Strategies to circumvent the poor stability of metal oxide electrodes involve control of the melt oxobasicity with admixtures (eg, rare earth or alkaline carbonates/oxides), but also formation of solid solutions based on conventional NiO with other metals . The state‐of‐the art solutions show some efficacy, but alternative materials with high conductivity and chemically stable are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Within a significant list of tested electrode materials, the best area specific resistance (ASR) values are in the order of 0.1 Ω.cm 2 at 550°C, using a standard LiNiO 2 cathode. A few complex chemical compositions show ASR values about twice to three times higher in the 500°C to 550°C range.…”
Section: Introductionmentioning
confidence: 99%
“…The SOFCs having operation temperature ≤650°C are known as LT‐SOFCs. It is reported that LT‐SOFCs have greater efficiency for energy conversion under partial load circumstance, reduced corrosion, and sealing problems and have stability for longer span . These are used to provide electric power for mobile devices and are expected to provide energy having lower content of carbon .…”
Section: Classification Of Sofc Anodesmentioning
confidence: 99%
“…It is reported that LT-SOFCs have greater efficiency for energy conversion under partial load circumstance, reduced corrosion, and sealing problems Cu-CeO 2 cermet 700°C 51 Greater ionic and electronic conductivity 82 Ni-GDC IT-SOFC 83 No deposition of carbon Nickel is subjected to oxidation 84 Ni/CGO IT-SOFC 74 and have stability for longer span. 97 These are used to provide electric power for mobile devices and are expected to provide energy having lower content of carbon. 31 Low temperature SOFC anodes have maximum value of power density, 77 which leads to the reduction in cost of material and cell fabrication.…”
Section: Low Temperature Sofc (Lt-sofc) Anodesmentioning
confidence: 99%
“…Sun et al . investigated a novel perovskite‐like oxide for low‐temperature SOFCs operating at 400–600 °C. The authors demonstrated a power density exceeding 300 mW/cm 2 .…”
mentioning
confidence: 99%